Evaluation and implementation of good pratices in main points of microbiological contamination in milk production - Fagan, Éder Paulo; Beloti, Vanerli; Barros, Márcia A. F.; Muller, Ernst E.; Nero, Luís A.; Santana, Elsa H. W.; Magnani, Douglas Furtado; Vacarelli, Emanuel R.; Silva, Luiz C.; Pereira, Mykell S. (Semina: Ciências Agrárias, 2005)
In order to improve the microbiological quality of Brazilian milk and dairy products some measures have been implemented in the milk-producing sector throughout the years, such as milk refrigeration and bulk collection. Refrigeration is a very efficient procedure, however allows psychrotrophics multiplication, which are largely found in milk produced in poor hygienic conditions. To assure and improve the microbiologic quality of milk turns out to be necessary the implementation of hygienic measures, known as Good Manufacturing Practices (GMP). In this study, several hygienic practices were tested in the main contamination points in milk production, previously determined: teats (different chlorine concentrations pre-dipping), cans and bulk tanks (hygienic techniques) and residual water (elimination). The recommended practices were picked up considering their efficiency in microbial reduction, practiced and economic viability. When the practices were all applied, reduction in microbial counts was observed. After 48 hours the final and refrigerated milk showed a reduction of 11.95x106 CFU/mL to 12.48x103 CFU/mL of mesophilic aerobes, and a reduction of 18.10x106 CFU/mL to 5.38x103 CFU/mL of psychrotrophics. The results show that the procedures proposed by LIPOA is efficient, viable and easily adopted by milk farmers, representing an important alternative in producing high quality milk.